Profitability of Guinean banking sector 2006 to 2018 - Saoulomou, Augustin (My University, 2021)
“PROFITABILITY OF GUINEAN BANKING SECTOR 2006 TO 2018” The purpose of this research is to investigate the profitability of the Guinean banking sector from 2006 to 2018. The research takes into consideration a fixed-effect model based on panel data which contains data of the commercial banks in activities in the Guinean banking sector. In terms of studying the level of cost efficiency of Guinean Commercial banks by the effect of endogenous and exogenous variables; the research provides a parametric method known as the stochastic border approach. This approach illustrates the determination of the variables which explain the level of inefficiency or efficiency. The Output of this research has a significant policy implication. Firstly, commercial banks of the sector are engaged in nontraditional activities for rising their profitability for the sake of increasing financial risk. Therefore, both central bank and policymakers need to regulate nontraditional activities of commercial banks to prevent the financial risk. Secondly, both Guinean central bank and commercial banks as main actors of the banking sector are guided to implement the deposit insurance system to respond to the stability of the financial system and then increase Guinean banks’ profitability. Moreover, Guinean commercial bank managers have to keep implementing the efficiency of the return of the banks’ assets, the banks' equity, and capital for both small, medium, and big banks of the sector. The results allow concluding that at which level each bank was more profitable and the corresponding factors. Key-words: Panel Data Analysis, Banking Sector, Guinean Banks, Profitability

GİNE BANKACILIK SEKTÖRÜNÜN KARLILIĞI 2006 - 2018 Bu araştırmanın amacı, Gine bankacılık sektörünün 2006'dan 2018'e kadar olan karlılığını incelemektir. Araştırma, Gine bankacılık sektörününün karlılığını ticari bankaların 2006-2018 verilerini kullanarak panel veri metodolojisi kapsamında sabit etkiler modeli ile analiz etmektedir. Araştırma, içsel ve dışsal değişkenler ile stokastik sınır yaklaşımı ve verimsizlik düzeyini (verimlilik) açıklayan değişkenlerin belirlenmesi olan parametrik bir yöntem sunmaktadır. Bu araştırmanın çıkarımları sıralanacak olursa; ilk olarak, ticari bankaların karlılığını artırmak ve finansal riskleri engellemek adına merkez bankası ve politika yapıcıları tarafından ticari bankaların geleneksel olmayan faaliyetleri regüle edilmelidir. İkinci olarak hem Gine merkez bankası hem de banka sektörünün ana aktörleri olan ticari bankalar, finansal sistemin istikrarına cevap vermek ve Gine bankalarının karlılığını artırmak adına mevduat sigortası sistemini uygulamalıdır. Dahası, Gine ticari banka yöneticileri, sektörün hem küçük- orta hem de büyük bankaları için bankaların varlıklarının, bankaların öz sermayesinin ve sermayesinin getirisinin verimliliğini amaç edinen uygulamalara devam etmelidir. Sonuçlar, her bir bankanın hangi seviyede daha karlı olduğu ve buna karşılık gelen faktörlerin sonucuna varılmasına olanak sağlamaktadır. Panel Veri Analizi, Bankacılık Sektörü, Gine Bankaları, Karlılık
Keywords: Bankacılık Sektörü; Bankalar ve bankacılık; Banking Sector; Banks and banking; Finance; Gine; Gine Bankaları; Guinean; Guinean Banks; Karlılık Panel Data Analysis; Maliye; Panel Veri Analizi; Profitability